Sex/Gender as a Factor That Influences Transcranial Magnetic Stimulation Treatment Outcome: Three Potential Biological Explanations - Hanlon, Colleen A.; McCalley, Daniel M. (Frontiers in Psychiatry, 2022)
Repetitive transcranial magnetic stimulation (rTMS) is a non-invasive brain stimulation technique which is now being used in psychiatry clinics across the world as a therapeutic tool for a variety of neural-circuit based disorders (e.g. major depression, obsessive compulsive disorder, addiction, headache, pain). The high volume of use has provided researchers with a unique opportunity to retrospectively evaluate factors influencing TMS treatment responses. While many studies have focused on TMS protocol parameters as moderators of treatment efficacy, a recent publication by Sackheim et al (2020) highlights another critical, often overlooked factor influencing TMS treatment outcome – sex/gender. Their findings extend a body of literature that supports the notion that women, especially during periods of high estradiol, are particularly sensitive to the therapeutic effects of rTMS. Drawing on literature from cranio-facial anatomy, neuroimaging, and neuroendocrine fields, we posit that observed increases in response rates of women in clinical rTMS trials may be related to: 1) closer proximity of the brain to the scalp at the prefrontal cortex, leading to larger TMS induced electric fields especially at the medial prefrontal cortex, 2) greater gray matter density and gyrification in the prefrontal cortex, and 3) high levels of estradiol which facilitate cortical excitability. These biological explanations are empirical ideas which lend themselves to prospective evaluation in multisite clinical rTMS trials. These 3 potential explanations all indicate that the TMS field should routinely evaluate sex/gender (and associated biological metrics like scalp-to-cortex distance, gray matter density, estradiol/progesterone levels) as a factor that may influence treatment outcome.